Endobronchial primary large B-cell Non-Hodgkin lymphoma in HIV-infected patient in the Highly Active Antiretroviral Therapy era: Description of a case report. (2017) - Caterino, U.; Tambaro, O.; Palmiero, G.; Borrelli, F.; Cotugno, M.; Bonadies, G.
Abstract: We report an unusual case of endobronchial primary large B-cell Non Hodgkin Lymphoma in a HIV-infected patient in the course of effective Highly Active Antiretroviral Therapy (HAART). Diagnosis of large B-cell NHL was obtained by fibreoptic bronchoscopy (FOB) biopsies. Three cycles of R-CHOP chemotherapy (rituximab, vincristine, cyclophosphamide, hydroxydaunorubicin, prednisone) was performed and clinical and radiological remission was obtained after 3 cycles of therapy.